Auto-Carto 9 : Ninth International Symposium on Computer-Assisted Cartography, Baltimore, Maryland, April 2-7 - Auto-Carto (9th 1989 Baltimore, Md.); American Society for Photogrammetry and Remote Sensing; American Congress on Surveying and Mapping (Falls Church, VA, USA : The Society, 1989)
29